Descriptores de la precipitación de la cuenca del río cachi de Ayacucho - Pereda, Alex (2024)
The study exposes the rainfall descriptors observed in the Cachi river basin, during 1991 to 2008, due to the nature of its development, it is quantitative descriptive, not experimental, longitudinal, acted on a chronological series of 3016 records of monthly precipitation in 22 hydrometeorological stations managed by the Regional Government of Ayacucho. The data were organized in Excel and processed in SPSS, then the analysis of variance was performed, applying descriptive statistics and multiple comparisons of Duncan, observing that at least one of the averages of the monthly rainfall is different from the others. The results revealed that, from 1991 to 1999, the average monthly rainfall in the basin showed small cyclical variations that denotes fluctuation from a very low level to a slightly high level, except for the year 1993 with an accentuated precipitation at a high level. In the other years of the period, precipitation shows greater variation with pronounced peaks located at a high and very high level; in addition, in the summer months the average monthly rainfall is the highest of the year, in the other months it is very low, especially in the months of May to July; Likewise, it was determined that precipitation in the Upper Basin varies from 18.97 to 98.00 mm and in the Middle Basin it ranges from 43.92 to 97.90 mm. With these estimates, the inverse relationship between precipitation and station altitude is not met.